Dynamic Mechanical Properties and Constitutive Model of Honeycomb Materials with Random Defects under Impact Loading - Hu Jun; Ren Jianwei; Ma Wei; Wang Aiguo (Shock and Vibration)
The study analyzed the influence of random defects on plateau stresses of honeycomb materials with varied relative densities and established a computational model of honeycomb materials considering random defects. The results show that the plateau stress decreases evidently as the random defects increase, which is closely related to the relative density of honeycomb materials. It also set up a functional relationship between relative plateau stresses and random defects as well as that between relative plateau stresses and relative densities. Taken topological structure, random defects and strain rate effect into consideration, and it proposed a dynamic constitutive model of honeycomb materials under low-middle impact loading. And the proposed constitutive model possesses a better applicability to match the stress-strain relationship of honeycomb materials in existing impact experiments. The proposed constitutive model could make a theoretical foundation in material design and practical application of honeycombs containing random defects.